Vortex as a means of improving educational aerodynamic characteristics of aircraft - Махмуд, А.Ф. (Proceedings of National Aviation University (archive), 2007)
Examine matter using the Vortex Generator like instrument for lead in hair angel of attack or for prevention tearing off turbulent flow boundary layer from component airplane without energy consumption.